Community policing’s extended military history: Brazilian pacification from the Global Cold War to the Global War on Terror - Müller, Markus-Michael (Policing and society, 2021)
This article analyses the frequently neglected synergies, past and present, between community-oriented policing (COP) and community-centred military interventions in Latin America. From the vantage point of Brazilian pacification efforts, from the Global Cold War to the Global War on Terror, it is argued that COP is a transnational security governance rationale that emerged during the Global Cold War out of the discovery of the ‘community’ as a key target for military interventions seeking to counter the presence of non-state armed actors challenging state authority. This underlying logic survived the end of the Cold War, including in Latin America. In the post-9/11 context COP efforts returned to their militarized Cold War origins, when local security bureaucracies (re)discovered the usefulness of engaging with local communities in order to confront challenges to state power from non-stated armed actors, such as gangs and drug traffickers. This argument will be elaborated through an analysis of on one of the most recent Latin American COP ‘success stories’: the pacification programme operating in Rio de Janeiro since 2008. Drawing on historical and contemporary policy documents, as well as multi-sited empirical fieldwork, the transnational historical entanglements of domestic and external pacification experiences will be highlighted, allowing us to point towards the negative potentials of militarising COP efforts in regards to the inclusiveness of democratic security governance.